Childhood Adversity Trajectories and Violent Behaviors in Adolescence and Early Adulthood. Issue 15 (August 2022) - Salo, Madeleine; Appleton, Allison A.; Tracy, Melissa
Violence and other antisocial behaviors, including fighting and weapon carrying, are highly prevalent among adolescents but usually decrease in young adulthood. Childhood adversities, including exposure to abuse, intimate partner violence, and household substance use and mental health problems, have been linked to violent behaviors in adolescence and adulthood. However, few studies of childhood adversity as determinants of persistent violent behavior among community-based samples have been conducted. Furthermore, the effects of adversity timing and duration on subsequent violent behaviors are unclear. We examined the association between five childhood adversity trajectories (representing stable-low, stable-mild, decreasing, increasing, and stable-high adversity from birth through age 11.5 years) and physical fighting and weapon carrying at ages 13-20 years among a sample of young adults followed continuously since birth from the Avon Longitudinal Study of Parents and Children ( n = 9, 665). The prevalence of violent behaviors declined sharply as participants aged (e.g., whereas 42.8% reported engaging in physical fighting in the past year at ages 13-15 years, this dropped to 10.4% at ages 17-20 years). Childhood adversity trajectories exhibited a strong dose-response relation with physical fighting and weapon carrying, with particularly pronounced relations for violent behaviors persisting across both adolescence and early adulthood (e.g., for physical fighting at both ages 13-15 years and 17-20 years compared to no fighting at either period, adjusted odds ratio [aOR] = 1.62, 95% confidence interval [CI] = 1.31-2.00 for stable-mild; aOR = 2.33, 95% CI = 1.64-3.33 for decreasing; aOR = 3.18, 95% CI = 2.20-4.60 for increasing; and aOR = 3.73, 95% CI = 2.13-6.52 for stable-high adversity, compared to stable-low adversity). This work highlights the substantial implications of exposure to childhood adversity for youth violence prevention.